Limiting rival's efficiency via conditional discounts - Katja Greer (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2013)
This paper studies the impact of a dominant firm's conditional discounts on competitors' learning-by-doing. In a vertical context where a dominant upstream supplier and a competitive fringe sell their products to a single downstream firm, we analyze whether the dominant supplier prefers to offer a discount scheme, as in particular a quantity or market-share discount. In a dynamic setting with complete information and learning-by-doing, short-term market-share discounts and long-run contracts are more profitable to the dominant supplier than simple two-part tariffs or quantity discounts. We show that two-part tariffs as well as quantity discounts lead to more learning than market-share discounts, or long-term contracts. Thus, the dominant firm's contract choice restricts the competitive fringe's efficiency gain. Similar results occur for network effects.
Keywords: L13; L42; 330; Market-share discounts; quantity discounts; learning-by-doing; dominant upstream supplier; competitive fringe.